Use of modified freeze-drop ball test for ınvestigation the crack propagation rate in coal mining- case study for the şırnak asphaltite shale, marly shale and marl in Şırnak coal site - Tosun, Yıldırım İsmail (KTÜ Karadeniz Teknik Üniversitesi, 2016)
Use modified freeze-drop ball test was used for investigation of the crack propagation rate in tunneling and coal mining- case study for the coal shale, marly shale and marl in Şırnak city coal site. The coal mine excavations create the roof disturbances greater the issue to encounter in situ ground operation conditions. The roof rock shale and coal contacts in underground space makes an inadequate strength and safety issue of the operation work is more difficult, especially in water absorption concern of coal side rock. The lump-size marl, marly shale and shale rock types and distribution and compression were investigated by modified freeze test regarding the conditions in the post excavation field of coal by time. Rocklab and Stereonet7 programs performed with four types of rock and crack propagation analysis for A1, A2, A3 and A4 types of rock were investigated. Anisotropy of rocks and mixture models were tested in laboratory scale. Heterogeneous crack parameters were analyzed. Regarding the analysis, shale and marly shale type rocks, A1, A2 were poor to stable state that showed greater rate crack propagation to be high safety risk. However, anisotropic layer of limestone in marly shale through water absorption exhibited lower stability in coal contacts as seen in coal sites. Because of growing demand, the high safety condition of mine excavation site is required and has to be concerned. In the stable ground, the cracked side rock has to be covered and supported in order to avoid consolidation and rock bursting. This modified test also measures the impact resistance of rocks tested for use in the scaling to 30-40 cm lump massive rock models in laboratory to provide face scale to 2-3 m. The indentation by the drilling bit enters in-situ the massive lump rock, where the volume of rock retained can regulate through the advance rate. Depending on the resistivity of the rock volume in the head distance, the indentation pressure can be controlled.
Keywords: Drop Ball Test; Freeze Cracking; Crack Cementing; Crack Strengthening